Fight disciplines in physical education undergraduate courses: analysis in Brazilian higher education institutions - Pereira, M. P. V. C.; Folle, A.; Pereira, N.; Cirino, C.; Mota, I. D.; Scaglia, A. J.; Farias, G. O. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2023)
Background. The teaching of fighting arts in initial training in Physical Education mostly uses disciplines which focus on common fighting modalities and few are identified as mandatory disciplines in the curriculum. Problem and aim. Analyze the proposals for fight disciplines in Brazilian public universities, considering their nomenclatures, syllabus, bibliographies and character. Methods. The study is qualitative in nature, characterized as descriptive, as a source of documentary information. Results. In the results, 131 disciplines corresponding to fighting and martial arts were found. Of these, 80 syllabuses were accessed and analyzed subdivided into categories, highlighting the predominance of the conceptual aspects of fighting and martial arts in the syllabus descriptions. The analysis of the bibliography was carried out across 12 disciplines, highlighting the predominance of specific literature by modalities of fighting and martial arts. In addition, the results also identified the number of mandatory (54) and elective (26) subjects. Conclusion. The analyzed HEIs present different disciplines related to fighting and martial arts in their curricular matrices. It is therefore suggested that HEIs promote actions that enrich the contents of their disciplines around fighting arts.